Hubungan Kecanduan Smartphone, Jenis Kelamin dan Usia terhadap Kecemasan pada Mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar Angkatan 2020, 2021 dan 2022 - I Putu Andre Wibawa Saputra; Danang Nur Adiwibawa; Nurkomariah Zulhijjah; Lusiana Wahyu Ratna Wijayanti (Malahayati Nursing Journal, 2026)
ABSTRACT Anxiety is described as an unpleasant mood condition accompanied by a subjective feeling of uncertainty and threat in the future. There are two factors that can influence anxiety, namely internal factors (gender, age, level of education, and experience in care) and external factors (medical condition/disease diagnosis, access to information, therapeutic communication, environment, health facilities, threat), conflict. (contradictory), approach (approach), avoidance (evasion), fear (fear of missing out on information, for example resulting from smartphone addiction) and unfulfilled need (needs that are not met). Anxiety disorders can occur at all ages, more often in adulthood. Anxiety is common among medical students. Globally, medical students have a prevalence of anxiety (41.6%) followed by depression (36%). Meanwhile in Indonesia anxiety reaches 22.4%, and female students experience moderate to severe levels of anxiety compared to female students. men, of which 91.6% experienced anxiety. This research was conducted to find out whether there is a relationship between smartphone addiction, gender and age and anxiety among students at the Faculty of Medicine, Al-Azhar Islamic University Class of 2020, 2021 and 2022. The type of research used is observational analytics using a cross sectional study research design. The sampling technique uses stratified random sampling. This research was carried out at the Faculty of Medicine, Al-Azhar Islamic University. The data obtained were analyzed using the chi-square test.In the bivariate analysis, the results showed that there was a significant relationship between age and smartphone addiction on anxiety with a p-value of 0.000. There was no relationship found between gender and anxiety with a p-value of 0.289. Based on the results of statistical tests carried out, there is a relationship between age and Smartphone addiction and anxiety among students at the Faculty of Medicine, Al-Azhar University Class of 2020, 2021 and 2022. However, no relationship was found between gender and anxiety among students at the Faculty of Medicine, Al-Azhar University. Classes of 2020, 2021 and 2022. Keywords: Age, Gender, Smartphone Addiction, Anxiety.  ABSTRAK Kecemasan digambarkan sebagai kondisi mood yang tidak menyenangkan disertai rasa subyektif tentang ketidakpastian dan ancaman di masa depan. Terdpat dua faktor yang dapat mempengaruhi kecemasan yaitu faktor internal (jenis kelamin, usia, tingkat pendidikan, dan pengalaman di rawat) dan eksternal (kondisi medis/diagnosis penyakit, akses informasi, komunikasi terapeutik, lingkungan, fasilitas kesehatan, threat (ancaman), conflict(pertentangan), approach (pendekatan), avoidance (pengelakan), fear (ketakutan akan tertinggal suatu informasi contohnya yang di akibatkan karna kecanduan Smartphone) dan unfuled need (kebutuhan yang tidak terpenuhi). Gangguan kecemasan dapat terjadi pada semua usia, lebih sering pada usia dewasa. Kecemasan umum terjadi pada mahasiswa kedokteran. Secara global, mahasiswa kedokteran memiliki prevalensi kecemasan (41.6%) yang diikuti adanya depresi (36%). Sedangkan di Indonesia kecemasannya mencapai 22.4%, dan mahasiswa perempuan mengalami kecemasan tingkat sedang hingga berat dibanding mahasiswa laki-laki, dimana 91.6% mengalami kecemasan. Penelitian ini dilakukan untuk mengetahui apakah terdapat hubungan kecanduan Smartphone, jenis kelamin dan usia terhadap kecemasan pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar Angkatan 2020, 2021 dan 2022. Jenis penelitian yang digunakan adalah analitik observasional dengan menggunakan rancangan penelitian cross sectional study. Teknik pengambilan sampel menggunakan stratified random sampling. Penelitian ini dilaksanakan di Fakultas Kedokteran Universitas Islam Al-Azhar . Data yang diperoleh dianalisis dengan uji chi-square. Karakteristik responden sebagian besar di dominasi oleh anak remaja usia 19-20 tahun dan jenis kelamin laki-laki. Pada analisis bivariat didapatkan hasil bahwa terdapat hubungan yang signifikan antara usia dan kecanduan smartphone terhadap kecemasan dengan p-value 0,000. Tidak ditemukan hubungan antara jenis kelamin terhadap kecemasaan dengan p-value 0,289. Berdasarkan hasil uji statistik yang dilakukan, terdapat hubungan antara usia dan kecanduan Smartphoneterhadap Kecemasan pada Mahasiswa Fakultas Kedokteran Universitas al-azhar Angkatan 2020, 2021 dan 2022. Namun tidak ditemukan hubungan antara jenis kelamin terhadap kecemasan pada Mahasiswa Fakultas Kedokteran Universitas al-azhar Angkatan 2020, 2021 dan 2022. Kata Kunci : Usia, Jenis Kelamin, Kecanduan Smartphone, Kecemasan.